Managing Sounds in the Operating Room Improving Patient Care Using Active and Passive Noise Control - DAĞCI M.; Öztekin S. D.; YEŞİLTAŞ S. (My University, 2025)
Sounds are used to communicate, whereas noise is an unwanted or unpleasant sound. Each of these can be perceived differently by humans and nonhumans and in different situations. In operating rooms (ORs), high levels of sound perceived as noise can increase patient stress levels and delay recovery from surgery, which has a negative impact on the treatment process. Active and passive noise control methods must be implemented to ensure patient safety during surgery. Active noise control uses computer technology to create counter-phase sound waves by listening to sounds within the environment. Passive noise control aims to reduce noise through soundproofing and dampening. Each method has its own advantages and disadvantages; however, the use of both methods in the OR can provide a quieter, safer, and more patient-focused environment for surgical care. The aim of this review was to explain the effects on patients of environmental noise within the OR and the importance of using individual noise control for these patients.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Ortopedi ve Travmatoloji; Hemşirelik; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Orthopedics and Traumatology; Nursing; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Ortopedi; Clinical Medicine (Med); Clinical Medicine; Orthopedics; Ortopedi ve Spor Hekimliği; İleri ve Uzman Hemşirelik; Orthopedics and Sports Medicine; Advanced and Specialized Nursing; noise; noise control; operating room noise; perioperative patient care